2012
DOI: 10.1016/j.healun.2011.11.023
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of measuring cardiac preservation injury demonstrates University of Wisconsin solution is associated with less ischemic necrosis than Celsior in early cardiac allograft biopsy specimens

Abstract: Purpose No consensus exists on the optimal heart preservative solution (HPS) for cardiac allograft preservation. The significance of varying degrees of acute ischemic necrosis (AIN) in early transplant biopsies is unknown. We investigated the effects of HPS on early cardiac histopathology by developing a novel grading system of AIN. Methods We retrospectively reviewed our institutional database of orthotopic heart transplants (OHT) identifying all hearts preserved with University of Wisconsin (UW) or Celsior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Although there may be some variability in the composition of individual centers’ solutions, the use of Celsior or cardioplege were both significant predictors of adverse recipient outcomes in our analysis compared to preservation with University of Wisconsin solution. Other studies have found similar interactions suggesting that the use of these solutions should be questioned during cardiac procurement (21, 22). Given that myocardial protection is paramount in the field of heart transplantation, further study into the biochemical interactions associated with each preservative solution as well as the development of new solutions will further delineate the optimal preservation strategy in order to minimize myocardial injury during organ transport.…”
Section: Discussionmentioning
confidence: 67%
“…Although there may be some variability in the composition of individual centers’ solutions, the use of Celsior or cardioplege were both significant predictors of adverse recipient outcomes in our analysis compared to preservation with University of Wisconsin solution. Other studies have found similar interactions suggesting that the use of these solutions should be questioned during cardiac procurement (21, 22). Given that myocardial protection is paramount in the field of heart transplantation, further study into the biochemical interactions associated with each preservative solution as well as the development of new solutions will further delineate the optimal preservation strategy in order to minimize myocardial injury during organ transport.…”
Section: Discussionmentioning
confidence: 67%
“…Aside from preexisting PAH in the recipient, ischemia and reperfusion injury associated with organ preservation can also contribute to RVF after CTX. Various heart preservation solutions are commercially available, some of which may play a role in ischemia and right HF . Finally, longer cold ischemia time and advanced donor age can also lead to a weaker RV and increase the risk of postoperative failure …”
Section: Pathophysiologymentioning
confidence: 99%
“…Compared with Celsior preservation solution, UW is associated with less ischemic necrosis in early cardiac allograft biopsies [89] and improved short-term outcomes [90]. UW was superior to histidine-tryptophan-ketoglutarate (HTK) solution after prolonged cold preservation of renal grafts [91] but inferior to Celsior in liver transplantation associated with more post-reperfusion syndrome [92].…”
Section: Clinical Applicationmentioning
confidence: 99%